The Role of the Dynamic Financial Liquidity Ratios in Corporate Management - Białas, Katarzyna (Journal of Finance and Financial Law, 2017)
Purpose – The purpose of this article is to identify the role and importance of the data on the financial liquidity achieved through standard, static liquidity ratios, and the alternative, dynamic liquidity ratios, from the point of view of the company management. Research Methodology – In the article was made an analysis of financial data of company X quoted on the Warsaw Stock Exchange from the point of view of liquidity management. This analysis was carried out in two variants: static and dynamic. Result – The study evaluated the usefulness of the information of data indicators from the point of view of management and strategic cash management in the context of maximizing profits for the owners. Originality/value – The study rated the indicator values are the real reflect the current situation of the company. This information allows management to rational financial management which enables the timely repayment, financing of investments and long-term development of the market.